The role of social media in tourism - Mirhamidova Gulibonu (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This annotation explores the impact of social media on the tourism industry, focusing on how platforms like Facebook, Instagram, Twitter, and YouTube have transformed the way travelers discover, plan, and experience travel. It discusses the role of social media in inspiring wanderlust, influencing travel decisions, and shaping travel trends through user-generated content and influencer marketing. The annotation also highlights the importance of social media for tourism businesses and destinations in marketing their offerings, engaging with customers, and providing real-time customer service. Overall, it emphasizes the significant role of social media as a powerful tool for connecting travelers, businesses, and destinations, and enhancing the overall travel experience